Effect of Pitavastatin on Sterol and Bile Acid Excretion in Guinea Pigs - Aokia, Taro; Yamazakia, Hiroyuki; Maejimaa, Takashi; Sato, Fumiyasu; Kitaharab, Masaki; Saito, Yasushi (Arzneimittelforschung, 2003)
The influence of pitavastatin (CAS 147526-32-7), a potent 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitor, exerted on fecal and biliary excretion of sterols and bile acids was investigated using guinea pigs. The cumulative amount of [3H] bile acid in bile 0 to 6 h after the injection of high density lipoprotein (HDL), which was labeled with [3H] cholesteryl ester (CE), was slightly decreased with atorvastatin (30 mg/kg, CAS 134523-00-5) and simvastatin (30 mg/kg, CAS 79902-63-9), and the same level as the control was maintained with pitavastatin (3 mg/kg). The amount of excretion of [3H] sterol into bile was significantly increased with atorvastatin and simvastatin, and exhibited a tendency to decline with pitavastatin. The [3H] bile acid/ [3H] sterol ratios were significantly lowered with atorvastatin and simvastatin by 41 % and 29 %, respectively, as compared to the control, and exhibited an upward tendency with pitavastatin (22 %). The total amounts of fecal [3H] bile acid from 0 to 7 days were significantly decreased with atorvastatin and simvastatin by 30 % and 32 %, respectively, and slightly increased with pitavastatin by 8 % Furthermore, mRNA expression of the hepatic microsomal cytochrome P-450 enzyme, cholesterol-NADPH : oxygen oxidoreductase (cholesterol 7 α-hydroxylase; CYP7A), which is a late limiting enzyme with a bile acid composition, was also decreased with atorvastatin and simvastatin by 54 % and 38 %, respectively, and slightly increased with pitavastatin (14 %). The change in CYP7A mRNA expression was well correlated with the amount of the fecal [3H] bileacid. The bile acid excreting efficacy of pitavastatin was relatively high as compared with atorvastatin or simvastatin. It is suggested that this action may contribute to the powerful cholesterol lowering action of pitavastatin.
Keywords: CAS 147526-32-7; 3-Hydroxy-3-methylglutarylcoenzyme A reductase inhibitor; Pitavastatin, bile acid excretion, cholesterol; 7a-hydroxylase, guinea pig